2013
DOI: 10.3745/jips.2013.9.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Semantic Image Retrieval

Abstract: Abstract-The big challenge in current content-based image retrieval systems is to reduce the semantic gap between the low level-features and high-level concepts. In this paper, we have proposed a novel framework for efficient image retrieval to improve the retrieval results significantly as a means to addressing this problem. In our proposed method, we first extracted a strong set of image features by using the dual-tree rotated complex wavelet filters (DT-RCWF) and dual tree-complex wavelet transform (DT-CWT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Wavelet analysis is one of the most important methods for extracting a signal from any data [17][18][19][20]. The Wavelets de-noising application has been widely used.…”
Section: Noise Reduction By Wavelet Threshold Functionmentioning
confidence: 99%
“…Wavelet analysis is one of the most important methods for extracting a signal from any data [17][18][19][20]. The Wavelets de-noising application has been widely used.…”
Section: Noise Reduction By Wavelet Threshold Functionmentioning
confidence: 99%
“…최근 문서 검색 [1,2], 이미지 매칭 [3], 바이오 시퀀스 매 칭 [4] [14]. 회전-불변 매칭 [15,16]은 이미지가 회전되더라도 동일한 매칭 결과를 얻는 방법으로 [7,9] (2) R1 := RI_Matching(Q, DB, ε); //rotation-invariant m atching using the original query sequence Q.…”
Section: 서 론1 )unclassified
“…Lindstaedt et al [6] proposed visual folksonomy based automatic image tagging especially for fruits and vegetables. In addition, Manh and Lee [7] focus on small object segmentation based on visual saliency in natural images and Divya et al [8], Santosh and Shyam [9], and Patil and Kokare [10] demonstrated that image segmentation and automatic image tagging models help with semantic image retrieval.…”
Section: Related Researchesmentioning
confidence: 99%